MUSUH ALAMI KUTU PUTIH Paracoccus marginatus Williams & Granara de Willink, (HEMIPTERA: PSEUDOCOCCIDAE) PADA TANAMAN PEPAYA DI MINAHASA UTARA - Tairas, Robert W.; Tulung, Max; Pelealu, Jantje (EUGENIA, 2015)
ABSTRACT The potential of biological control using natural enemies locally has a huge opportunity, therefore, carried out a study in order to determine the types of natural enemies of both predators, parasitoids and pathogens on the mealybug P. marginatus live in papaya plants in North Minahasa area. The study found that in Minahasa north, there are natural enemies comprised of predators, pathogens and parasitoids, among others, Chilocorus sp. Scymnus sp. (Coleoptera), Oecophylla smaragdina and some of the family Formicidae (Hymenoptera), earwig (Dermaptera), mites (Acari) and Tetragnatha sp, Tetragnatidae; Plexippus sp. Telamonia sp; Lycosidae (Aranea). At the parasitoid was found only Acerophagus papayae, family Encyrtidae (Hymenoptera), while natural enemies of pathogen is Fungus Keywords : P. marginatus, mealybugs, natural enemies, predators, parasitoid and pathogen